Quantum Field Theory: Competitive Models - Fauser, Bertfried; Tolksdorf, Jürgen; Zeidler, Eberhard (SpringerLink Bücher, 2009)
The present volume emerged from the 3rd `Blaubeuren Workshop: Recent Developments in Quantum Field Theory', held in July 2007 at the Max Planck Institute of Mathematics in the Sciences in Leipzig/Germany. All of the contributions are committed to the idea of this workshop series: To bring together outstanding experts working in the field of mathematics and physics to discuss in an open atmosphere the fundamental questions at the frontier of theoretical physics.